Simulação, controle e avaliação das configurações de troca térmica no processo de desidratação de etanol em reator de leito fixo - Miranda, Hiago Vieira de (2017)
Ethylene is one of the most used monomers in the formation of petrochemicals. Due to the oil crisis in the 1970s, the expansion of new ways of obtaining ethylene was necessary, and processes previously little explored industrially began to be studied, in particular the process of catalytic dehydration of ethanol in fixed bed reactors. The process has major advantage in environmental matters, especially in the reduction of gas emissions that are responsible for the greenhouse effect, as opposed to more conventional processes, such as the cracking of naphtha. For processes in fixed bed reactors, the need to promote heat transfer properly can be a challenge, since a deficiency in the temperature regulation can lead to serious operating problems, such as termination of the reaction, low conversions or favoring secondary reactions. In this context, this work has as objectives the simulation of a fixed bed reactor model for ethanol dehydration reaction to ethylene, the verification of the effect of thermal fluid settings (co-current and countercurrent) and the implementation of a strategy of control for the reactor temperature. The countercurrent configuration provided higher conversion of ethanol and ethylene production under the evaluated operational conditions. The results of the simulations are in accordance with the literature. The temperature control at the cold spot of the reactor proved effective in reducing the effects generated by disturbances in the heating fluid feed temperature. Moreover, the PI controller also showed quick and smooth response to set point changes.